Treatment of Fraley’s syndrome by upper-pole nephrectomy - Cerqueira, Thaís Bandeira; Lima, Natalia Bacellar Costa; Baptista Neto, Romeu Magno; Moreira Filho, José Cohim; Café, Luiz Eduardo (São Paulo Medical Journal, 2007)
CONTEXT: Fraley’s syndrome is characterized by vascular compression on the superior infundibulum with secondary dilatation of the upper pole calyx, mostly located on the right side. CASE REPORT: We present the case of a 22-year-old woman with vascular compression of the upper-pole infundibulocalyceal system (Fraley’s syndrome). The patient had a history of frequent hospitalizations for emergency care due to lumbar pain over the past twelve months. The diagnosis was obtained following renal arteriography. Since the surgical treatment by means of upper-pole nephrectomy, the patient has not had any further symptoms.